A ternary nanocatalyst of Ni/Cr/Co oxides with high activity and stability for alkaline glucose electrooxidation. (20th February 2016) - Gu, Yingying; Yang, Haihong; Li, Benqiang; An, Yarui
Highlights: Ni-Cr-Co nanomaterial was synthesized by thermal decomposition method. Ni4 -Cr1 -Co1.5 has the highest GOR activity among the prepared catalysts. A catalytic current density of 23.8 mA × cm −2 is attained for alkaline GOR. Abstract: A novel ternary nanocatalyst of Ni-Cr-Co oxides is synthesized as anode electro-catalysts for glucose oxidation. The nanostructure is characterized by X-ray diffraction (XRD) and scanning electron microscope (SEM), which indicates that the catalyst particles are well dispersed with average size of 30 nm when the calcination temperature is 500 °C. The electrochemical performance is evaluated via cyclic voltammetry (CV). Compared with the bimetallic Ni-Cr and Ni-Co nanocatalysts, Ni-Cr-Co electrocatalysts exhibites more negative onset potential (0.4 V) and high oxidation peak current density (23.8 mA cm −2 ) in alkaline media towards glucose oxidation. Meanwhile, the results also show that the Ni-Cr-Co nanomaterial possesses good performance of anti-poisoning capability, reproducibility and long-time stability, which make it an excellent candidate for fuel cell electrocatalyst.